COVID-19 lockdowns have imposed substantial economic costs on countries in Africa - Thurlow, James (International Food Policy Research Institute, 2020)
It is too soon to assess the full economic impacts that COVID-19 lockdowns will have on developing countries. But early research indicates that many African economies are significantly impacted and that poorer households are struggling. IFPRI is conducting a series of country studies, in collaboration with local and government partners, that use economywide models to estimate the impacts of lockdowns, assess the exposure of food systems, and identify vulnerable population groups.